Phytochemical and biological evaluation of methanolic extract of Boehmeria macrophylla leaves - Tahmid, Tasin (BRAC University, 2019)
This project report is submitted in partial fulfilment of the requirements for the degree of Bachelor of Pharmacy, 2018.